Oxygenic Phototrophs Need ζ-Carotene Isomerase (Z-ISO) for Carotene Synthesis: Functional Analysis in Arthrospira and Euglena. (8th October 2019) - Sugiyama, Kenjiro; Takahashi, Koh; Nakazawa, Keisuke; Yamada, Masaharu; Kato, Shota; Shinomura, Tomoko; Nagashima, Yoshiki; Suzuki, Hideyuki; Ara, Takeshi; Harada, Jiro; Takaichi, Shinichi
Abstract: For carotenogenesis, two biosynthetic pathways from phytoene to lycopene are known. Most bacteria and fungi require only phytoene desaturase (PDS, CrtI), whereas land plants require four enzymes: PDS (CrtP), ζ-carotene desaturase (ZDS, CrtQ), ζ-carotene isomerase (Z-ISO) and cis -carotene isomerase (CrtISO, CrtH). The gene encoding Z-ISO has been functionally identified in only two species, Arabidopsis thaliana and Zea mays, and has been little studied in other organisms. In this study, we found that the deduced amino acid sequences of Arthrospira Z-ISO and Euglena Z-ISO have 58% and 62% identity, respectively, with functional Z-ISO from Arabidopsis . We studied the function of Z-ISO genes from the cyanobacterium Arthrospira platensis and eukaryotic microalga Euglena gracilis . The Z-ISO genes of Arthrospira and Euglena were transformed into Escherichia coli strains that produced mainly 9, 15, 9′- tri-cis -ζ-carotene in darkness. In the resulting E. coli transformants cultured under darkness, 9, 9′- di-cis -ζ-carotene was accumulated predominantly as Z-ISO in Arabidopsis . This indicates that the Z-ISO genes were involved in the isomerization of 9, 15, 9′- tri-cis -ζ-carotene to 9, 9′- di-cis -ζ-carotene in darkness. This is the first functional analysis of Z-ISO as a ζ-carotene isomerase in cyanobacteria and eukaryotic microalgae. Green sulfur bacteria and Chloracidobacterium also use CrtP, CrtQ and CrtH for lycopene synthesis as cyanobacteria, but their genomes did not comprise Z-ISO genes. Consequently, Z-ISO is needed in oxygenic phototrophs, whereas it is not found in anoxygenic species.